THE ROLE OF SOCIAL MEDIA IN PROMOTING WOMEN’S EMPOWERMENT IN AFGHANISTAN - Karimi, Zahra; Zara, Bushra; Karimi, Roya; Quraishi, Tamanna (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study investigates the role of social media in empowering female students enrolled in an online university in Afghanistan. Despite ongoing socio-cultural restrictions that limit Afghan women’s access to education, employment, and public engagement, digital platforms present new avenues for empowerment. Using a quantitative survey design, data were collected from 110 female students aged 20–25 across three academic programs: Computer Science, Economics, and Medical Sciences. A structured questionnaire measured four empowerment dimensions—educational, economic, social, and digital—using a 5-point Likert scale. The results reveal strong educational empowerment, with respondents indicating that social media enhances access to academic resources, collaboration, and motivation for further studies. Social participation also showed significant improvement, as students reported increased confidence in communication and engagement with online communities. Digital literacy and self-efficacy were notably high, reflecting the positive impact of regular digital platform use. However, economic empowerment scored moderately, suggesting that although social media provides exposure to entrepreneurial opportunities, broader structural barriers still limit financial independence. Overall, the findings demonstrate that social media is a transformative tool for promoting women’s empowerment in Afghanistan. The study recommends enhancing digital literacy programs and expanding online economic opportunities to maximize empowerment outcomes.